ANALISIS PERAN GURU TERHADAP PEMBINAAN KEBIASAAN ANAK INDONESIA HEBAT DI SEKOLAH DASAR - Sindy Sepriani Amelia; Rizki Ananda; M. Syahrul Rizal; Iis Aprinawati; Yusnira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education in elementary schools serves as a crucial foundation for shaping a generation with noble character and positive personality. This study aims to analyze the role of teachers in fostering the 7 Habits of Great Indonesian Children at UPT SDN 009 Bangkinang Kota. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving teachers and the school principal. The findings reveal that teachers have a general understanding of the 7 habits, although the depth of understanding is not entirely uniform. Strategies applied include role modeling, positive reinforcement, integrating values into lessons, using creative media, and assigning roles to students to build responsibility. Challenges faced include the lack of specialized training, limited parental involvement, and insufficient facilities to support character building. Positive impacts observed include increased discipline, responsibility, care, and positive thinking habits among students. The school has provided support through policies and guidance, yet systematic strengthening and continuous teacher training are still needed. In conclusion, character building through the 7 Habits of Great Indonesian Children can be effectively implemented when supported by synergy between teachers, the school, and parents